A administração e o Brasil: as figuras do gestor, do colonizador e a imagem paterna - Bresler, Ricardo Rocha Brito (2000)
This thesis has its starting point in an ethnography that we realized from decemberj94 to februaryj95 in a carpenter shop called Chácara Cogumelo, through the participatory research method. From the reality we have experienced (breathed), we have identified the domination· entailments of this shop floor directly connected to the father/son situation, that drove us to remit to the wider phenomenon of organizational power in Brazil. It analysis the social division process, of unequal social conditions and the exclusion process that we observe and we argue it dwells: in the separation of the intellectual and manual knowledge that is intrinsic to management practices in our system, in a wider sense; in the peculiar colonization process through the action represented by the figure of the slavery explorer, in the national context. It stands out the violence, the resistance and the conflicts that exists in the relations managers/subordinates, settlers/slavers through the interpretation of material and symbolic conditions that sustains these dialectics. From this base, it propose an analogy among the figures represented by the manager and the settler, through the paternal image.